SHOULDER ARTHROPLASTY REHABILITATION - Burcu Yanık,; Gülay Dinçer, (Archives of Rheumatology, 2004)
The glenohumeral joint has the greatest amount of motion of any joint in the body. The first aim of the shoulder arthroplasty is to decrease the pain. The loss of joint motion and function are the other indications. Rehabilitation after shoulder arthroplasty depends on multiple factors, including the status of the soft tissues around the shoulder (intact or torn rotator cuff, size of tear), the quality of the bone, the stability of the implant and the fixation technique used, any concomitant injuries or systemic illness, and the expectations of the patient.